Pemikiran Pembebasan dalam Teologi (Suatu Analisis Historis dan Geografis) - M. Husein A. Wahab (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
Issues on liberation in all religions lead to emerge a lot of thinkers both in orthodox and modern theology. These issues aims at not making a doctrine or creed an absolute way of life for a believer or an absolute conduct for a citizen. In historical perspective, absolute doctrine or creed is usually made by a dictator for his or her permanently political power. Consequently, a believer or a citizen in one community is hampered in communication and not tolerant to the other believer or to other community. This rigid condition, at the end, usually leads to criticism and protest of some critical thinkers either to the religious elites or the rulers of one country. To mention, there are some theological liberation sects or movements: rational theology, transformative theology, contextual theology, humanism, Dalif and Minjung. In politics, the super power or developed countries produce maps as geographical perspective to divide, to limit, to control and to rule under developed countries either in economy, social, cultural and religion. Asia, Africa and Latin America are supposed to be the third worlds (poor countries) under the control of super powers as rich countries.